The Role of the First Instance Tribunal in Transmitting Acts to the Appellate Court: Canons 1615; 1621; 1625; 1630-1632; and 1679-1680 - Daneels, Frans (Roman Replies and CLSA Advisory Opinions 2016, 2016)
The following letter was forwarded by the Secretary of the Apostolic Signatura, with the acknowledgment that the difficulties encountered in the case might be of interest and practical value to canonists. The letter, addressed to a bishop and moderator of a tribunal, affirms the role of a first instance tribunal in transmitting acts to the appellate tribunal, dispels the practice of setting peremptory time limits on tribunal fees, and asserts that a first instance sentence may not become immediately executive if the prescribed fifteen day period of possible appeal - among other requirements of the law - is not met.